Current experimental methods to investigate the impact of specialized pro-resolving lipid mediators on Sjögren’s syndrome - dos Santos, Harim T.; Nam, Kihoon; Gil, Diana; Yellepeddi, Venkata; Baker, Olga J. (Frontiers in Immunology, 2023)
Sjögren’s syndrome is a chronic inflammatory autoimmune disease characterized by diminished secretory function of the exocrine glands. Although extensive investigation has been done to understand Sjögren's syndrome, the causes of the disease are as yet unknown and treatments remain largely ineffective, with established therapeutic interventions being limited to use of saliva substitutes with modest effectiveness. A primary feature of Sjögren’s syndrome is uncontrolled inflammation of exocrine tissues and previous studies have demonstrated that lipid-based specialized pro-resolving mediators reduce inflammation and restores tissue integrity in salivary glands. However, these studies are limited to a single specialized pro-resolving lipid mediators family member resolvin D1 or RvD1 and its aspirin-triggered epimer, AT-RvD1. Consequently, additional studies are needed to explore the potential benefits of other members of the specialized pro-resolving lipid mediators family and related molecules (e.g., additional resolvin subtypes as well as lipoxins, maresins and protectins). In support of this goal, the current review aims to briefly describe the range of current experimental methods to investigate the impact of specialized pro-resolving lipid mediators on Sjögren’s syndrome, including both strengths and weaknesses of each approach where this information is known. With this article, the possibilities presented by specialized pro-resolving lipid mediators will be introduced to a wider audience in immunology and practical advice is given to researchers who may wish to take up this work.